2021
DOI: 10.3390/app112412106
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Dissolution of Stainless-Steel Slag Minerals in Different Acid Environments to Promote Their Use for the Treatment of Acidic Wastewaters

Abstract: Several stainless-steel slags have been successfully employed in previous studies as substitutes for lime in the treatment of industrial acidic wastewaters. This study deepens the knowledge of such application, by analyzing the neutralizing capacity of different slags related to their mineral compositions. To do so, firstly the chemical and mineral compositions of all the slag samples are assessed. Then, 0.5 g, 1 g, 2 g of each slag and 0.25 g and 0.5 g of lime are used to neutralize 100 g of 0.1 M HCl or HNO3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…One of the fundamental minerals utilized for producing those types of biomaterials is merwinite [9,36,37]. It generally demonstrated low to partial solubility in a variety of test conditions [38,39]. The ceramics containing this mineral have exhibited high reactivity in SBFs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the fundamental minerals utilized for producing those types of biomaterials is merwinite [9,36,37]. It generally demonstrated low to partial solubility in a variety of test conditions [38,39]. The ceramics containing this mineral have exhibited high reactivity in SBFs.…”
Section: Discussionmentioning
confidence: 99%
“…Merwinite is composed of Mg 2+ , Ca 2+ , and SiO 4 4ions; its crystal structure is [MgO 6 ] octahedral, linked at every corner by [SiO 4 ] tetrahedra [40]. Overall, it exhibits greater stability than the mineral-crystal structure of certain other minerals, such as such as dicalcium silicate and bredigite [38], and probably hatrurite (which consists of Ca 2+ ions and SiO 5 polyhedra). According to Galal et al, ProRoot MTA showed higher solubility compared to Harvard MTA [9].…”
Section: Discussionmentioning
confidence: 99%
“…It may also be possible recycle gallium through separation of a gallium concentrate from the LED through grinding down and selective electrostatic separation. 124 125…”
Section: Waste Streams and Systems For Recyclingmentioning
confidence: 99%
“…De Colle et al [4] analysed the neutralizing capacity of different slags related to their mineral compositions to promote their use as alternative materials for the treatment of acidic wastewaters.…”
Section: Contributionsmentioning
confidence: 99%